CuO nanostructure by oxidization of copper thin films - Raksa P. (2014)
CuO nanostructures were synthesized by oxidizing copper thin films. The copper thin film was grown on alumina substrates by evaporation copper powder at pressure of 0.04 mtorr. The copper thin films were then oxidized 800, and 900°C for 12, 24 and 48 hr, respectively. The obtained CuO nanostructures were investigated by Energy Dispersive Spectroscopy (EDS), Field Emission Scanning Electron Microscope (FE-SEM) image, and X-Ray Diffraction (XRD). The diameter of CuO nanostructure is around 100-600 nanometers and it is depends on oxidation reaction time and temperature. These CuO nanostructures have a potential application for nanodevices such as nano gas sensor or dye-sensitized solar cells. © 2008 Trans Tech Publications, Switzerland.